2004
DOI: 10.1103/physrevb.70.245423
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and dephasing in a two-dimensional electron gas at intermediate conductances

Abstract: We study, both theoretically and experimentally, the negative magnetoresistance (MR) of a twodimensional (2D) electron gas in a weak transverse magnetic field B. The analysis is carried out in a wide range of zero-B conductances g (measured in units of e 2 /h), including the range of intermediate conductances, g ∼ 1. Interpretation of the experimental results obtained for a 2D electron gas in GaAs/InxGa1−xAs/GaAs single quantum well structures is based on the theory which takes into account terms of higher ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 90 publications
6
49
0
1
Order By: Relevance
“…Such a temperature dependence is very similar to what has been observed in Ref. 74 for similar values of k F l e . In that work, 74 the exponent varied from p = −0.5 to −0.3 when reducing k F l e Ͻ 5 down to k F l e ϳ 1, similar to our observations.…”
Section: ͑16͒supporting
confidence: 83%
See 1 more Smart Citation
“…Such a temperature dependence is very similar to what has been observed in Ref. 74 for similar values of k F l e . In that work, 74 the exponent varied from p = −0.5 to −0.3 when reducing k F l e Ͻ 5 down to k F l e ϳ 1, similar to our observations.…”
Section: ͑16͒supporting
confidence: 83%
“…[69][70][71][72][73][74][75][76][77] In such 2D systems, an estimation of the localization length loc 2D is given by 74,75 loc…”
Section: A 2d Hall Barsmentioning
confidence: 99%
“…The Hikami-Larkin Naganoka theory describing weak localization(and anti-localization) effects assumes diffusive motion of electrons, and predicts the magnitude of weak anti-localization to be αe 2 /(2π ), where α = 0.5 is a fixed constant per independent electronic channel. This is however not valid in the pseudo-diffsuive regime, where it has been shown that α = 0.5−2R/π, where R is the sample resistance in units of e 2 /h [68,69]. This suppression of α is a consequence of pseudo-diffusive transport where quantum corrections to conductance need to take into account terms in higher orders of the dimensionless conductance g = 1/R.…”
Section: Gate Tunable Suppression Of Weak-antilocalizationmentioning
confidence: 96%
“…where ( ) = ( 1 2 + 1 ) + ln with the limiting cases ( ) ≈ 2 /24 for ≪ 1 and for ≫ 1 ( ) ≈ ln − 2 ln 2 − + 2 2 ⁄ , with = 0.5772 is the Euler constant [24,29]. Moreover, since is much smaller than any other time scales here [25], the excess conductance can therefore be simplified to…”
Section: Magnetoconductancementioning
confidence: 99%